CURRENT STATE OF THE PROBLEM OF SURGICAL TREATMENT IN PATIENTS WITH VARICOCELE - N.D. MUKHIDDINOV; M.KH. MALIKOV; KH.S. ODINAEV; Z.R. ABDULLOEV (Avicenna Tajik State Medical University, 2017)
The article presents modern aspects of surgical treatment of varicocele, comparison of various techniques of operative interventions in this pathology, as well as further optimization management of patients with this disease. Given all the data studied in the analysis of contemporary literature, issue improving testimony for performing individual methods in surgical treatment remains relevant and require additional research.